Dissociative recombination of the CH+ molecular ion at low energy. (25th April 2018) - Chakrabarti, K; Mezei, J Zs; Motapon, O; Faure, A; Dulieu, O; Hassouni, K; Schneider, I F
Abstract: The reactive collision of the CH + molecular ion with an electron is studied in the framework of the multichannel quantum defect theory, taking into account the contribution of the core-excited Rydberg states. In addition to the X 1 Σ + ground state of the ion, we also consider the contribution to the dynamics of the a 3 Π and A 1 Π excited states of CH + . Our results—in the case of the dissociative recombination in good agreement with the storage ring measurements—rely on decisive improvements—complete account of the ionisation channels and accurate evaluation of the reaction matrix—of a previously used model.